SOLVING THE STUDENTS’ PROBLEM IN WRITING DESCRIPTIVE TEXT THROUGH ATTRIBUTE CHARTS STRATEGY - M. Fadhly Farhy Abbas; Shelvira Elsa Dwita (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2019)
This research was based on the students’ problems in writing descriptive text, especially in terms of organizing the generic structure, determining adjective to describe people or things, and mastering vocabulary. The purposes of this research were to improve the students’ writing skill in descriptive text and to find out the factors influencing the students’ improvement through Attribute Chart strategy at grade 7.2 of SMPIT Al Birru Pekanbaru. The design of this research was Classroom Action Research. The instruments used were the writing test, observation checklist, field note, and interview. The participants involved in this research were the students at grade 7.2 which was consisted of 16 students. The result showed that the students base score was 51.8, and the score in cycle 1 was 70.4. It means the students’ score was improved in cycle 1. Furthermore this improvement was influenced by 4 factors. These factors were obtained based on the result of field note. Moreover, the results of field note were: students’ motivation, students’ interest, students’ exciting with the new topic, and the students’ activeness in the learning process. In conclusion, the use of Attribute Chart strategy in writing descriptive text can improve students’ writing skill at 7.2 grade of SMPIT Al Birru Pekanbaru.